Analysis of Conflict Management and Internal Communication on Employee Satisfaction in Creative Industries in Indonesia - Sunardi Ginting; Irwan Amar; Dyah Palupiningtyas; Fahruni Khaerunnisa; Yayu Rakkang (West Science Social and Humanities Studies, 2024)
This study examines the impact of conflict management and internal communication on employee satisfaction within the creative industries in Indonesia. Utilizing a quantitative research design, data were collected from 150 employees using a structured questionnaire featuring a Likert scale ranging from 1 to 5. The analysis was conducted using Structural Equation Modeling-Partial Least Squares (SEM-PLS 3) to test the proposed hypotheses. The findings indicate that effective conflict management significantly enhances employee satisfaction, with clear and consistent internal communication further amplifying this effect. Additionally, internal communication was found to moderate the relationship between conflict management and employee satisfaction, highlighting its critical role in fostering a positive work environment. These results suggest that fostering a harmonious work environment and promoting transparent communication channels are crucial for improving employee satisfaction in the creative sector. This study contributes to the literature by providing empirical evidence on the relationships between conflict management, internal communication, and employee satisfaction, offering valuable insights for practitioners and policymakers aiming to enhance organizational performance in the creative industries.